Gogol i kot - Skaczkowa, Olga (Przegląd Rusycystyczny, 2011)
GOGOL AND CAT Summary Long before Fiodor Dostojevski Nikolai Gogol had been reflecting on the destructive ef-fect of murder on the murderer’s mind. As a child of five he killed a homeless cat and could not help thinking and speaking about that event further on. By this he should have tried to change the pattern of his destiny, to re-arrange his life, which started in rather barbarous surrounding ruled by primitive instincts and ignorant fears. He longed for another, humane and enlightened social environment in which an individual would live in the current of his-tory and culture, willingly shouldering responsibility for the world’s harmony, being aware that other living creatures could not be regarded as food supplies or enemies but as friends and teachers. GOGOL I KOT Streszczenie Na długo przed Dostojewskim Gogol rozmyślał o tym, jak zabójstwo wpływa na psychikę zabójcy. Opowiadając o przestępstwie dokonanym w wieku pięciu lat — o zabiciu kota — najpewniej usiłuje przeformułować paradygmat swoich relacji ze światem, wyjść z rzeczywistości ciemnego środowiska otaczającego go w dzieciństwie, rzeczywistości -rodziny, w której prymitywne instynkty sąsiadowały z lękami zrodzonymi przez niewiedzę, i przejść do rzeczywistości oświeconego Zachodu, gdzie człowiek żyje w strumieniu historii i kultury, dobrowolnie przyjmując odpowiedzialność za utrwalenie harmonii wszystkiego, co istnieje, w której zwierzęta są nie tylko pożywieniem lub wrogiem, lecz stają się też nauczycielami.